G267 Improving the Quality of Hospital Discharge in Babies with Down Syndrome: Part One of a Quality Improvement Study. (24th May 2017) - Moore, CM; Eldaw, S; McCormack, M; Fitzsimons, J
Abstract : Aims: This review aims to assess the compliance with the acknowledged national guidelines on the medical management of Down Syndrome from the period from birth to six weeks of age in a regional neonatal centre. These guidelines recommend accepted standards of care for children with Down Syndrome. Method: This was a retrospective review. Babies with Down Syndrome were identified from the Maternity Information System (Maternity Live) over the preceding three years. Charts were retrieved and reviewed. Results: There were 19 babies diagnosed with Down Syndrome identified from the Maternity Information System with a discharge diagnosis of Down Syndrome identified from the Maternity Information System. All babies in our review had a postnatal diagnosis of trisomy 21 with no suspicions of chromosomal anomaly noted on the antenatal imaging, with no antenatal screening or testing performed. Table 1 demonstrates the compliance with different standards of care as per the Medical Management of Down Syndrome guidelines. Conclusions: Compliance with Medical Management of Down Syndrome guidelines is less than expected. We plan to pilot a proforma for insertion in the chart when babies are clinically diagnosed with trisomy 21 in order to ensure complete care of babies with Down Syndrome, and to standardise our proforma with other centres across our regional network.